Wild boars (Sus scrofa) affect the recruitment rate and spatial distribution of holm oak (Quercus ilex) - Gómez, Jose M.; Hódar, José a. (Forest Ecology and Management, 2008)
The role of herbivores in controlling plant population abundance and distribution is unclear. We experimentally determine the effect of damage by wild boars (Sus scrofa) in recruitment rate and spatial pattern of a Mediterranean tree, the holm oak (Quercus ilex). We monitored oak establishment in the Sierra Nevada of southeastern Spain during 4 years (1999–2002) in four plots, two fenced and two unfenced that were used as controls. In addition, we planted 1-year-old seedlings in all microhabitats, both in fenced and control plots, to experimentally determine the effect of wild boar on their microhabitat-dependent survival. Despite seedling abundance being similar inside and outside the fences, sapling abundance diminished up to 50% in unfenced plots compared to fenced plots. Wild boars also seemed to modify the spatial distribution of seedlings and saplings. Whereas seedlings were most abundant under pines both in fenced and control plots, sapling abundance was highest under pine trees in fenced plots, but similarly abundant under pines or shrubs in control plots. This change in spatial pattern was due to the effect of wild boars killing seedlings when looking for food under pines. The effects of the different mortality factors were not additive. Where ungulates are absent, recruitment is high and occurs under oaks and especially under pines. Where wild boars are present, recruitment diminishes and occurs mostly under shrubs and pines. Wild boars arrest population growth and modify the spatial pattern of recruitment.
Keywords: Facilitation; herbivory; Population regeneration; Quercus ilex; Seedling establishment limitation; Seedling recruitment; Wild boars